Pengaruh Kualitas Produk, Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Kopi Kenangan - Nur Dalilah; Prawoto Prawoto (MAMEN: Jurnal Manajemen, 2023)
Currently, coffee is a type of global drink that is well-known in the world. Coffee is a very well-known commodity throughout Indonesia. Coffee, which used to be synonymous with men and adults, recently young people and even women are increasingly fond of drinking coffee. Along with the increase in coffee consumption from year to year, the coffee shop business has also experienced a significant increase. Each coffee shop must be adept at managing its business by having various concepts to attract the attention of customers. The aim of this research is to increase customer satisfaction at Kopi Kenangan by focusing on the role of product quality, promotion, and service quality. Using IBM Statistics Version 26, evaluate the research hypotheses. Purposive sampling was used to collect a sample of 100 customers, and the results show that product quality has a positive impact on customer satisfaction while promotion has a positive impact and service quality does not. Taken together, product quality and promotion have a real and significant impact on customer satisfaction. Therefore the purpose of this research is to improve product quality and promotional efforts at Kopi Kenangan in order to better meet consumer needs and increase customer satisfaction.